Influenza B virus infection alters the regenerative potential of murine alveolar type 2 pneumocytes - Satoko Nakano; Cait E. Hamele; Aleksandra Tata; Purushothama Rao Tata; Nicholas S. Heaton (mBio)
ABSTRACT Respiratory epithelial cells can survive direct infection by influenza viruses, and the long-term consequences of that infection have been characterized in a subset of proximal airway cell types. The impact on the cells that survive viral infection in the distal lung epithelia, however, is much less well-characterized. Utilizing a Cre-expressing influenza B virus (IBV) and a lox-stop-lox tdTomato reporter mouse model, we identified that alveolar type 2 (AT2) pneumocytes, a progenitor cell type in the distal lung, can survive viral infection. We show that survival of infection is associated with transcriptional dysregulation compared to bystander AT2 pneumocytes from the same lung. Furthermore, ex vivo experiments revealed a significant reduction in proliferation rates in survivor AT2 pneumocytes compared to matched, non-directly infected bystander cells. Our findings not only enhance our understanding of the AT2 pneumocyte response to IBV infection but could also have broader implications for the mechanisms of respiratory epithelial repair post-viral infection.IMPORTANCEAlveolar type 2 (AT2) pneumocytes are a cell type critical for repair of the distal lung after an injury, such as a viral infection. After epithelial damage, AT2 pneumocytes proliferate for both self-renewal and differentiation into type I pneumocytes to repopulate the epithelium. Theoretically, some of the long-term lung sequelae associated with viral infections could be the result of inappropriate AT2 behavior. Here, the authors report that during an influenza B virus infection, some of the actively infected AT2 pneumocytes can ultimately eliminate all traces of the viral RNA and persist in the host long term. As a consequence of having been infected, however, the cells display an altered transcriptional profile and decreased proliferative capacity. These data together suggest a mechanism for how an acute viral infection can have long-term impacts on the pulmonary system.